Megapro Motorcycle Exhaust Gas Test Results - Wahyu Alif Ramadhan; Bahtiar Wilantara; Sulistia Aji Budi Utomo; Mohamad Saifudin; Benowo Randy Arsyad; Lukman Novaludin; M Fatkhur Rokhmanin (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2021)
This study presents the testing of a 4 stroke motorcycle engine on the effect of power, torque and exhaust emissions. The process of improving engine performance is to expand the piston stroke and increase the volume of air in the intake and fuel lines to the engine combustion chamber. The process is carried out by overstroke which increases the step volume by increasing the length of the piston so that the compression ratio increases, and oversizes the combustion chamber with a larger size to 200 cc. The test was carried out at the Automotive Mechanical Engineering Workshop at the Dharma Patria Polytechnic, Kebumen. The test was repeated 3 times to get maximum results. The research objective is to improve engine performance seen from data on power, torque and exhaust emissions obtained from testing using a gas analyzer. In this study, direct testing was carried out on a gas analyzer engine with three conditions, namely at rpm 1000, rpm 2000 and rpm 3000. The test results with a modified gas analyzer engine show 41 ppm HC and 4.3% CO levels, these numbers indicate better exhaust gas levels.